Theoretical themes in management and management accounting in China / Yu Xu-Ying - Yu, Xu-Ying (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
This paper explores four related themes in management and management accounting from a Chinese perspective. First, it describes how the basis of management has shifted from a material to a human focus, where culture is emphasized. Second, it explains several factors that tend to make the value of professional services increase with time. Third, the paper looks at the implications of these developments for the management accountant and argues that a new management decision support theory with unique Chinese cultural characteristics needs to be developed as the core of a new management accounting system.